High food quality increases infection of Gammarus pulex (Crustacea: Amphipoda) by the acanthocephalan parasite Pomphorhynchus laevis. Issue 10 (September 2019) - Sanchez-Thirion, Kevin; Danger, Michael; Bec, Alexandre; Billoir, Elise; Labaude, Sophie; Rigaud, Thierry; Beisel, Jean-Nicolas; Felten, Vincent
Graphical abstract: Highlights: Higher quality resources increased gammarid survival and growth. Higher quality resources increased the proportion of infected gammarids. Higher quality resources led to more frequent multi-infections. Resource quality did not modulate parasite impacts on hosts' behavior. Anthropogenic-induced changes in resource quality might influence parasite development. Abstract: Parasitism is an important process in ecosystems, but has been largely neglected in ecosystem research. However, parasites are involved in most trophic links in food webs with, in turn, a major role in community structure and ecosystem processes. Several studies have shown that higher nutrient availability in ecosystems tends to increase the prevalence of parasites. Yet, most of these studies focused on resource availability, whereas studies investigating resource quality remain scarce. In this study, we tested the impact of the quality of host food resources on infection by parasites, as well as on the consequences for the host. Three resources were used to individually feed Gammarus pulex (Crustacea: Amphipoda) experimentally infected or not infected with the acanthocephalan species Pomphorhynchus laevis : microbially conditioned leaf litter without phosphorus input (standard resource); microbially conditioned leaf litter enriched in phosphorus; and microbially conditioned leaf litter without phosphorus input but complemented with additional inputs of benthic diatoms rich in both phosphorus and eicosapentaenoic acid. During the 110 day experiment, infection rate, parasite load, host survival, and parasite-mediated behavioral traits implicated in trophic transmission were measured (refuge use, geotaxis and locomotor activity). The resources of higher quality, regardless of the infection status, reduced gammarid mortality and increased gammarid growth. In addition, higher quality resources increased the proportion of infected gammarids, and led to more cases of multi-infections. While slightly modifying the geotaxis behavior of uninfected gammarids, resource quality did not modulate the impact of parasites on host behavior. Finally, for most parameters, consumption of algal resources had a greater impact than did phosphorus-enriched leaf litter. Therefore, manipulation of resource quality significantly affected host–parasite relationships, which stressed the need for future research to investigate in natura the relationships between resource availability, resource quality and parasite prevalence.